Tools for assessing of business receivables and payables (Economics and region, 2020)
The method of assessing the appropriateness of paying deferred payments to buyers in terms of comparisons of costs and revenues, proposed by scientists of Kyiv National University of Trade and Economics Mazaraki A.A. and Lihonenko L.A., is investigated and its toolkit for estimating the value of receivables and payables is used as an example of the enterprise Poltava Oil-Extraction Plant – Kernel Group, PJSC in 2019. The level of expenditure and income of the enterprise is determined taking into account various factors, and the absolute amount of the effect of the receivables and payables is calculated. The valuation of creditor debt as an element of capital is based on the general concept of the value of capital. The capital prices refer to the relative annual cost of servicing debt to suppliers, investors. The value of the commodity payables is determined on the basis of an estimate of the losses from underpayment of the price discounts that would have been available to businesses in making advance payments. The effectiveness of debts is determined and «balance of value» is analyzed. This made it possible to establish that at Poltava Oil-Extraction Plant – Kernel Group, PJSC in 2019 the effect of lending to consumers in receivables exceeds the results obtained from the use of the accounts payable. However, in order to minimize the «cash gap» the enterprise is advised to use factoring and bill payments, which are reasonably effective tools in the management of payables and receivables, giving discounts to buyers.
Keywords: receivables; payables; capital values; valuation tools; consumers; enterprises; expenses; revenues